Investigation of cpa. and zpx. Genes in Cronobacter sakazakii Isolation from Clinical Specimens in Thi-Qar Province (Medico Legal Update, 2020)
Cronobacter sakazakii is a member of Enterobactereacae family and it is a food-born pathogenic bacteria which can cause several diseases for human and animals. The present study focused on the isolation of this species from clinical specimens from different sexes and ages in addition to hospital environments specimens and then investigation of cpa. and zpx genes. The specimens have been taken from group of hospitals in Al-Nasiriyah city (center of Thi-Qar province- south of Iraq). The identification was done by both phenotypical methods and confirmed by API. 20 E. system. Then investigation of cpa. and zpx. genes by conventional PCR.Out of 400 specimens (100 from each Burn humans, stool of patients with diarrhea, urine with UTI. in addition to hospital environments specimens) there were 16 (4 %) of specimens gave positive for C. sakazakii included : 4 from 100 burns specimens (4%), 6 from 100 stool specimens (6%), 0 from 100 urine (0%) and 6 from 100 hospital environments specimens (6%). The 16 isolates have been tested for presence of cpa. and zpx. genes by PCR., a number of 13 (81.25%) and 16 (100%) gave positive for these genes respectively. This species was exist in the clinical specimens and can cause diarrhea and burn infection in the area of study with ratio equal to what obtain by other researchers. Additionally this species considered hazardous because of having the cpa. and zpx. genes